2014
DOI: 10.1021/jf502412f
|View full text |Cite
|
Sign up to set email alerts
|

Novel Peptide with a Specific Calcium-Binding Capacity from Whey Protein Hydrolysate and the Possible Chelating Mode

Abstract: A novel peptide with a specific calcium-binding capacity was isolated from whey protein hydrolysates. The isolation procedures included diethylaminoethyl (DEAE) anion-exchange chromatography, Sephadex G-25 gel filtration, and reversed-phase high-performance liquid chromatography (HPLC). A peptide with a molecular mass of 237.99 Da was identified by liquid chromatography-electrospray ionization/mass spectrometry (LC-ESI/MS), and its amino acid sequence was confirmed to be Gly-Tyr. The calcium-binding capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 35 publications
(63 reference statements)
3
68
0
Order By: Relevance
“…A research found that the α‐helix in the secondary structure of the lysozyme was destroyed and then the absorption intensity of UV absorption spectrum decreased obviously (Zhao & Yang, ). A similar research has reported that the UV absorption of the peptide was increased, and its spatial structure was changed after the chelation of Gly‐Tyr with metal ions (Zhao et al, ). The absorption peak of QWFH at 250–300 nm, the characteristic absorption of conjugated structure (such as benzene) in the residues of Trp and Phe, was detected, indicating that the microenvironment of the amino acid (Trp and Phe) residues was affected.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…A research found that the α‐helix in the secondary structure of the lysozyme was destroyed and then the absorption intensity of UV absorption spectrum decreased obviously (Zhao & Yang, ). A similar research has reported that the UV absorption of the peptide was increased, and its spatial structure was changed after the chelation of Gly‐Tyr with metal ions (Zhao et al, ). The absorption peak of QWFH at 250–300 nm, the characteristic absorption of conjugated structure (such as benzene) in the residues of Trp and Phe, was detected, indicating that the microenvironment of the amino acid (Trp and Phe) residues was affected.…”
Section: Resultsmentioning
confidence: 74%
“…and its spatial structure was changed after the chelation of Gly-Tyr with metal ions (Zhao et al, 2014). The absorption peak of QWFH at 250-300 nm, the characteristic absorption of conjugated structure (such as benzene) in the residues of Trp and Phe, was detected, indicating that the microenvironment of the amino acid (Trp and Phe) residues was affected.…”
Section: Concentration Of Trolox MMmentioning
confidence: 99%
“…It was also observed that the band of 1451.23 cm −1 in the spectrum of the SCOHs moved to a lower frequency at 1441.91 cm −1 , which could be caused by the vibration of carboxylate group after the chelation. Besides, several absorption peaks for the SCOHs–Ca in the range 800–500 cm −1 arise from the vibration of the C–H and N–H bonds, and these bands disappeared in the SCOHs spectrum (Zhao et al ., ). These changes in bands indicated that the calcium binds to the SCOHs primarily via interactions with carboxyl oxygen and amino nitrogen atoms, which were similar to the peptide–calcium complexes derived from wheat germ protein hydrolysates (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…A novel peptide GlyTyr with a specific calcium-binding capacity was isolated from whey protein hydrolysate. The chelating mechanism of the peptide was investigated and the major binding sites were found to be the oxygen atom of the carbonyl group and nitrogen of the amino or imino group (Zhao et al 2014). This peptide might boost calcium absorption in the gastrointestinal tract and developing the peptide-calcium chelate as a supplement for enhanced calcium bioavailability seems promising.…”
Section: Gut Function and Prebioticmentioning
confidence: 99%